ANALYSIS OF THE APPLICATION OF EOQ AND POQ METHODS IN THE RAW MATERIAL INVENTORY CONTROL SYSTEM AT GRIYA BATIK MAS PEKALONGAN CITY - Izzati, Dini; Theresia Heni, Maria; Al Farizi, Musyafa (Politeknik Negeri Semarang, 2024)
Griya Batik Mas is a batik making industry still using conventional methods as its inventory control system. Purchases of fabric raw material supplies are carried out routinely with the same order quantity every month without taking into account the quantity required. To find out whether the method used has produced the best costs, a comparison is carried out by applying the Economic Order Quantity (EOQ) and Period Order Quantity (POQ) methods. Data collection methods through interviews, observation, and documentation with comparative and efficiency analysis. The results of this research show that there is a difference in inventory costs with savings in total inventory costsThe application of the Economic Order Quantity (EOQ) method is greater than that of the method Period Order Quantity(POQ) for the Griya Batik Mas inventory control system, which is Rp7,450,721 for the four types of fabric, with an order frequency of 5 times in 1 year.